The employee factor: perspectives on implementing enterprise social software. (2016) - Radi, Dania; Schlögl, Stephan; Leahr, Clint; Bernsteiner, Reinhard C.
Implementation strategies for enterprise social software (ESS) often focus too much on technical details and thereby neglect the need for understanding the employee perspective. Yet, the success of an implementation usually depends on the employees' attitudes towards the offered solution. The purpose of this paper is therefore to explore respective attitudes and identify associated challenges. A mixed research methodology combining a questionnaire study and expert interviews was used to explore user perspectives as well as current implementation practices of ESS. The results show that employees see ESS usage largely positive. Perceived benefits include less e-mail traffic, easier collaboration, more accessible expert knowledge, and lower communication barriers. However, it was also found that employees may be seen as the main challenge factor impeding a successful ESS implementation. In particular security concerns, the lack of guidelines, and the often missing appreciation for some of the benefits, may require an adequate communication strategy.